Professional service productization and its implications to knowledge transfer in internationalization processes –Case: Company X in Finnish, Swedish and Norwegian markets - Warro, Roope (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2016)
As a result of globalization, two thirds of the world’s business takes place nowadays in the service sector. In line, professional service firms are growing their share of the global service production. However, saturation of the professional service sector has forced professional service firms to search for more heuristic ways to conduct business in the international markets. By leveraging effectively the firm’s professionals, a professional service firm can lower its costs to clients and simultaneously generate additional value for the company and thus gain competitive advantage. Even though the academic field has shown growing interest towards services for decades, the fields of service productization and service internationalization are heavily understudied even today. Hence, the objective of this study was to contribute to the research on professional service internationalization and productization. The study concentrated on examining the impact that productization has on knowledge sharing and leveraging in professional service firms operating internationally. The research question focused on examining what implications productization has on knowledge transfer and leveraging during professional service internationalization by leaning on the existing research and on an empirical research. The empirical research was conducted as a single case study within a professional service firm operating in debt-related administrative service business. The case company is one of the leading operators in its field of business and therefore offered a fruitful environment to observe and analyze the topics in question. Additionally, the case company has a strong international presence and a large scale of operations in the selected markets, Finland, Norway and Sweden. Based on the previous literature and on the empirical research, this study found that for professional service firms to efficiently utilize individual, tacit knowledge, in its internationalization processes, it must be shared with the whole organization. By exploiting productization as a knowledge leveraging mechanism, a PSF can apply and transfer knowledge profoundly during its internationalization processes that would otherwise be difficult to tap into. Productization might not be sufficient alone, but by complementing it with a favorable organizational structure and culture, and by encouraging open communication, a PSF may take advantage of the whole potential that productization has to offer.